Florida Foliage House Plant Care: Adenium obesum - Richard J. Henny; Jianjun Chen (EDIS, 2013)
Adenium obesum and its many hybrids are often seen in retail garden centers. They have vibrant floral displays in shades of red, white, pink, and yellow. Flowers average 2–3 inches in diameter and may be single, double, or even triple. The plants must be stationed in high light, 6 hours or more per day, to maintain flowering during the summer. Adenium obesum makes a dramatic specimen for a deck or patio but should be moved indoors in winter. This 2-page fact sheet was written by R. J. Henny and J. Chen, and published by the UF Department of Environmental Horticulture, May 2013.